Ispol'zovanie priemov kata v soveršenstvovanii techniceskoj podgotovki sportsmenov-dzjudoistov - Sharina, E. P.; Moskalyonova, N. A.; Lagutenko, L. A.; Chumash, V. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Main priority directions in training and competitive activity of the sportsmen-judokas of childhood and adolescence age are the following: the motivation to training classes, and interest in judo, reduction of injuries, improvement of their technical training and entertainment for children and youth competitions. The article deals with the issues of improving the judo technique of athletes aged 9-12 years old according with the international trends from the standpoint of the purposeful use of complexes of sports. These changes are caused by the above-mentioned factors of development of modern children's and youth judo and the statement of additions to rules of competitions in judo for participants till 14 years.